PENGARUH RETURN ON ASSETS, DEBT TO EQUITY RATIO DAN KOMITE AUDIT TERHADAP AUDIT DELAY(Studi Empiris pada Emiten Sektor Properties & Real Estate yang terdaftar di Bursa Efek Indonesia periode 2019-2023) - Wardhani, Vyandha Angelisa Handina; Khasanah, Uswatun; Maidani, Maidani (SINERGI : Jurnal Riset Ilmiah, 2025)
The Effect of Return on Assets, Debt to Equity Ratio and the Audit Committee on Audit Delay (Empirical Study on Issuers  in the Properties & Real Estate  Sector Listed on the Indonesia Stock Exchange for the 2019-2023 Period). This study aims to test and analyze the influence of return on assets, debt to equity ratio and audit committee on audit delay. The population in this study is all issuers in the property & real estate sector  for the 2019-2023 period. The variables used in this study are audit delay as a dependent variable; return on assets, debt to equity ratio and the audit committee as independent variables. The sampling technique used the purposive sampling technique  and was obtained by 54 companies. The analysis methods used in this study are descriptive statistical analysis, panel data regression analysis, multiple linear regression test and hypothesis test. the results of the study show that return on assets, debt to equity ratio and the audit committee have a positive effect on audit delay.